THE EFFECT OF CURRENT RATIO, NET PROFIT MARGIN, AND RETURN ON ASSETS ON STOCK RETURN: (Study on Food and Beverages Companies Listed on the Indonesia Stock Exchange 2015-2017 Period) - Laila Siti Aminah (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2021)
Individuals and corporations investing in stocks should make sure the investments are appropriate before proceeding. It's also possible to use basic research or company performance as a substitute for investment appraisals. An investigation of the relationship between stock return and a company's current ratio, net profit margin, and return on assets was the primary goal of this research project (Study of Food and Beverages Companies Listed on the Indonesia Stock Exchange 2015-2017 Period). From 2015 to 2017, there were 21 Food and Beverage firms listed on the Indonesian Stock Exchange that were studied in this study. Purposive sampling was used to gather samples from 12 different Food and Beverage firms for this study. The SPSS 15 program was used to do multiple linear regression analysis on the data. The results of this study indicate that (1) Current Ratio (CR) with tstatistic = -2,244 and a significance value of 0,032 has a significant effect on stock returns; (2) Net Profit Margin (NPM) with tstatistic = -2,364 and a significance value of 0,024 has a significant effect on stock returns; (3) Return on Assets (ROA) with tstatistic = 3,984 and a significance value of 0,000 has a positive and significant effect on the value of stock returns.